(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2013)
Human Rights Education (HRE) has become one of the most important elements in human development, and has been upgraded to form part of general education in some countries. However, HRE has never been the main focus for the Bachelor of Laws programme in local universities in Malaysia except at the University of Malaya. This article will discuss the relationship between HRE and social unity. The analysis is entirely theoretical in nature. This article shows that HRE is an important instrument in maintaining social unity. Further, this article will discuss what would be the best method in designing a HRE syllabus in the Malaysian context. Keywords: education, human rights, social unity, Malaysia